Excitatory and inhibitory neuron imbalance in the intrauterine growth restricted fetal guinea pig brain: Relevance to the developmental origins of schizophrenia and autism. Issue 1 (24th November 2022) - Cumberland, Angela; Hale, Nadia; Azhan, Aminath; Gilchrist, Courtney P.; Chincarini, Ginevra; Tolcos, Mary
Abstract: Neurodevelopmental disorders such as schizophrenia and autism are thought to involve an imbalance of excitatory and inhibitory signaling in the brain. Intrauterine growth restriction (IUGR) is a risk factor for these disorders, with IUGR onset occurring during critical periods of neurodevelopment. The aim of this study was to determine the impact of IUGR on excitatory and inhibitory neurons of the fetal neocortex and hippocampus. Fetal brains ( n = 2) were first collected from an unoperated pregnant guinea pig at mid‐gestation (32 days of gestation [dg]; term ∼67 dg) to visualize excitatory (Ctip2) and inhibitory (calretinin [CR] and somatostatin [SST]) neurons via immunohistochemistry. Chronic placental insufficiency (CPI) was then induced via radial artery ablation at 30 dg in another cohort of pregnant guinea pigs ( n = 8) to generate IUGR fetuses (52 dg; n = 8); control fetuses (52 dg; n = 7) were from sham surgeries with no radial artery ablation. At 32 dg, Ctip2‐ and CR‐immunoreactive (IR) cells had populated the cerebral cortex, whereas SST‐IR cells had not, suggesting these neurons were yet to complete migration. At 52 dg, in IUGR versus control fetuses, there was a reduction in SST‐IR cell density in the cerebral cortex ( p = .0175) and hilus of the dentate gyrus ( p = .0035) but not the striatum ( p > .05). There was no difference between groups in the density of Ctip2‐IR (cortex) or CR‐IR (cortex, hippocampus) neurons ( p > 0.05). Thus, we propose that an imbalance in inhibitory (SST‐IR) and excitatory (Ctip2‐IR) neurons in the IUGR fetal guinea pig brain could lead to excitatory/inhibitory dysfunction commonly seen in neurodevelopmental disorders such as autism and schizophrenia.